Desertification dynamics in the Tarim Basin during 1990–2020 - YU Xiang; LEI Jiaqiang; GAO Xin; SUN Lingxiao; LYU Zhentao; Ireneusz MALIK; Malgorzata WISTUBA (Regional Sustainability)
Desertification poses a significant ecological threat to global sustainability, notably within arid regions such as the Tarim Basin surrounding the extensive Taklimakan Desert in Northwest China. This study used the Google Earth Engine (GEE) platform and Random Forest (RF) to analyze multi-temporal Landsat images to reveal desertification dynamics in the Tarim Basin spanning from 1990 to 2020. The results showed that land use types of the Tarim Basin were classified into three types: artificial oases, natural oases, and desertified land. To robustly quantify the spatiotemporal dynamics of land use, we introduced the Desertification Change Index (DCI), a novel metric specifically designed to measure the transformation sensitivity of land use types. Our analysis demonstrated that from 1990 to 2020, artificial oases showed a continuous increasing trend, while desertified land decreased significantly. Natural oases decreased during 1990–2000, then continued to grow, and showed a decreasing trend again after 2015. Moreover, natural oases have mainly been converted into desertified land and artificial oases. Artificial oases were mainly converted into natural oases, and most of desertified land was converted into natural oases. Regions with significant oasis expansion (DCI=2) were mostly concentrated within the influence radius of artificial oases. In contrast, regions with significant oasis degradation (DCI= –2) were generally farther from artificial oases. Finally, this study found that the changes in land use types of the Tarim Basin are mainly driven by human activities, which play a dual role—mitigating desertification by controlling oasis expansion and exacerbating desertification through unsustainable resource utilization. Ultimately, this research provides essential insights for policy-makers and land managers aiming to devise adaptive and sustainable desertification control measures in the Tarim Basin and similarly arid regions globally.